Pengaruh leverage, profitabilitas, ukuran perusahaan, kebijakan dividen, dan likuiditasterhadap nilai perusahaan - Wijayanti, Anisa Gusti; Susanto, Barkah; Pramita, Yulinda Devi (Borobudur Accounting Review, 2023)
This study aims to empirically test and analyze the effect of Leverage, Profitability, Firm Size, Dividend Policy, and Liquidity on Firm Value. The independent variables in this study are Leverage, Profitability, Firm Size, Dividend Policy, and Liquidity. The dependent variable in this study is firm value. The sample used in this study is property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The number of samples in this study is 55 of the total 11 companies. Determination of the sample obtained by using purposive sampling. Hypothesis testing is done by using regression analysis. The results of this study indicate that the Leverage and Profitability variables have a positive effect on firm value. While the variables of Firm Size, Dividend Policy, and Liquidity have no effect on firm value.